PARP Inhibitors for Sensitization of Alkylation Chemotherapy in Glioblastoma: Impact of Blood-Brain Barrier and Molecular Heterogeneity - Gupta, Shiv K.; Smith, Emily J.; Mladek, Ann C.; Tian, Shulan; Decker, Paul A.; Kizilbash, Sani H.; Kitange, Gaspar J.; Sarkaria, Jann N. (Frontiers in Oncology, 2019)
Prognosis of patients with glioblastoma (GBM) remains dismal despite maximal surgical resection followed by aggressive chemo-radiation therapy. Almost every GBM, regardless of genotype, relapses as aggressive recurrent disease. Sensitization of GBM cells to chemo-radiation is expected to extend survival of patients with GBM by enhancing treatment efficacy. The PARP family of enzymes has a pleiotropic role in DNA repair and metabolism and has emerged as an attractive target for sensitization of cancer cells to genotoxic therapies. However, despite promising results from a number of preclinical studies, progress of clinical trials involving PARP inhibitors (PARPI) has been slower in GBM. Preclinical in vivo studies have uncovered limitations of PARPI mediated targeting of base excision repair, considered to be the mechanism of sensitization for temozolomide (TMZ)- resistant GBM. Nevertheless, PARPI remains a promising sensitizing approach for at least a subset of GBM tumors that are inherently sensitive to TMZ. Our PDX preclinical trial helped delineate MGMT promoter hyper-methylation as a biomarker of PARPI veliparib mediated sensitization. In clinical trials, MGMT promoter hyper-methylation now is being studied as a potential predictive biomarker not only for response to TMZ therapy alone, but also PARPI mediated sensitization of TMZ therapy. Besides the combination approach being investigated, IDH1/2 mutant gliomas associated with 2-hydroxygluterate mediated homologous recombination (HR) defect may potentially benefit from PARPI monotherapy. In this article, we discuss existing results and provide additional data in support of potential alternative mechanisms of sensitization that would help identify potential biomarkers for PARPI based therapeutic approaches to GBM.